Taboo Words In The Youtube Law & Crime Network Of The Freak Off Party Case By P.Diddy: A Sociolinguistics Study - Silvia Sandi; Ervina Cm Simatupang (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
The research aims to classify types of taboo language and examine its media functions relevant to the "Freak Off" party planned by P Diddy on the Law&Crime Network YouTube. This study involves qualitative descriptive research. Emphasizing the qualitative descriptive technique is essential since it really focuses on investigating and comprehending the taboo language in relation to the social and cultural background of that taboo term. Video documentation on news coverage on the Law&Crime Network YouTube channel constitutes the data source. This study is based on Jay (2009) and Wardhaugh's (2010) theory. That information is phrases or utterances including prohibited terms. Data collecting methods are documentary study by recording video transcripts. Data analyses made use of the Miles and Huberman framework, which included data display, data reduction, and conclusion formulation. General data gathering techniques were theoretical and source triangulation data validation. Research on taboo words reveals that 3% of them are sexual taboos, namely Freak Off, Commercial Sex, and Masturbation. While legal and crime accounted for 6 percent, reference blackmail, narcotics, ketamine, and extortion; it also included violent forbidden terms, 3 percent drag, kick, and gun occurrences. Furthermore, taboo words serve purposes like attention-getting, theatrical, emotionally charged, and rule-breaking. The results showed that the law and criminal category (6%) was the most prevalent kind of taboo words, followed by violence taboo (3%) and sexual taboo (3%): blackmail, narcotics, masturbation and Kicked. In this particular setting, taboo language serves the following purposes: 1 - attract audience attention; 2 - express emotional intensities; 3 - emphasize legal and moral infractions; 4 - enhance rhetorical pr. The last of the four concerns their media coverage.This study is anticipated to help sociolinguistics mostly in terms of knowledge of taboo language use in digital media and whether or how it shapes public perceptions and media frames on social and criminal concerns